Breeding systems of the Paraguaná coastal plain plants, Venezuela - Lemus-Jiménez, Luis José; Ramírez, Nelson (Revista de Biología Tropical, 2005)
Breeding systems were evaluated for 51 plant species according to life form, pollination system, vegetation type, and phenology, in the coastal plain of Paraguaná Peninsula, Venezuela. Sexual systems were no associated to life form, pollination system, vegetation type, and phenology. The frequency distribution of sexual system was 82.3% hermaphroditism, 15.6% monoecy, and 1.9% dioecy. All sexual systems had a peak during the lowest rainfall. Genetic system distribution was 64.8% self-compatibility (including partially self-compatibility) and 35.2% self-incompatibility. Among self-compatible species, 45.1% were autogamous (19.6% not autogamous). The genetic systems were associated significantly to: (1) plant life form: self-compatible species tend to be herbaceous and self-incompatible plants tend to be woody species; (2) vegetation type: self-compatible species were predominant in the three vegetation types, but in the mangrove the frequency of self-compatible and self-incompatibles was similar; and (3) pollination system: most of the self-compatible species were polyphilous. Mating systems: xenogamous and autogamous species were associated only with plant life forms. Xenogamous plants were mostly woody species and autogamous plants were mostly herbaceous species. The high incidence of hermaphroditism, self-compatibility, and autogamy are related to herbaceous life form, polyphilous pollination system, and climatic conditions, together the insularity of the Paraguaná peninsula.